Polymerisation of α-Pinene Methacrylate monomer via Cobalt Mediated Catalytic Chain Transfer Polymerisation (CCTP) and Thiol Reactions to yield oligomers - Onat, Zeynep (2019)
Terpenes are renewable hydrocarbons found in nature. Their structural common characteristic is that they all contain unsaturated double bonds. However, early research has proven that homo polymerisation of these terpenes requires extreme conditions and results in low molecular weight polymers.1, 2 Modification of these terpenes in two steps via hydroboration/oxidation and esterification respectively to produce a library of terpene (methacrylates) was carried out in the group.1 In this study, α-Pinene Methacrylate (α-PMA) was the monomer under investigation.